Marketing with Social Media and Strengthening Identity Through Packaging Branding - Nugraha, Putu Gede Surya Cipta; Indrawan, I Putu Yoga (International Journal of Community Service Learning, 2021)
The purpose of this community service activity is to help partners take advantage of social media to expand market share, create business brands or logos as branding in strengthening business identity which will be implemented in product packaging. To achieve the objectives of the activity, the approach method used is interview and observation. The partner in this community service activity is a donut snack entrepreneur which is commonly consumed by children and adults as well as for religious activities. The results of the evaluation with partners on community service activities are that branding and packaging have a big role because partners get donut orders over the phone for religious ceremonies in the local area, where the phone number is obtained from the product packaging. The surrounding community also gave a positive response to social media partners who were used for product marketing. the conclusion of this community service activity went well. Partners are given increased knowledge about business management strategies so that they can continue to exist in the modern era by looking at social conditions, target consumers, current market conditions. Partners are given a business logo design that can be used by partners as a business product branding in the future. The implication obtained by partners is that the business market share is getting wider and builds consumer trust so that business profits increase.